A general approach for the intensive RFID reader deployment. (26th August 2014) - Zhou, Shijie; Luo, Jiaqing
We usually need to deploy a large number of readers to cover a certain area due to the limited read region of RFID readers. The challenge of the intensive reader deployment lies in that the collision among readers decreases the read rate and speed. In this paper, we propose a general approach to reduce the collision among readers and the number of readers. The basic idea of the approach is to maximise the coverage rate and minimise the overlapping rate. Such an approach contains two parts: grid–based model and PSO–based algorithm. We first build a grid–based model to describe both deployment area and read region. In particular, we divide them into small grids, and express grid graphs in a matrix form. Then, we propose a PSO–based algorithm to optimise the intensive reader deployment. Our simulation results show that the general approach can achieve high coverage rate and low overlapping rate.